On the Unique Significance of Han Yu’s "Shan Shi" - Jun, Tang (International Journal of Social Sciences and Public Administration, 2024)
As a representative work of Han Yu, "Shan Shi" is highly praised by Su Shi. This contains a distinct writing logic of temporal and spatial order, which makes reading immersive. In addition, the most eye-catching aspect of "Shan Shi" is its artistic technique of "reviving the spirit" and "incorporating literature into poetry", which has an irreplaceable and unique significance and role in the history of Chinese poetry.